1991
DOI: 10.1063/1.348868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen pressure on the synthesis of YBa2Cu3O7−x thin films by post-deposition annealing

Abstract: The effect of ambient oxygen pressure on the synthesis of epitaxial YBa2Cu3O7−x films on (100) SrTiO3 substrates by post-deposition annealing of amorphous precursor films was studied for oxygen partial pressures pO2 between 1.0 and 8.0×10−5 atm and annealing temperatures between 890 and 650 °C. A pO2−1/T diagram containing recent literature data regarding YBa2Cu3O7−x oxygen stoichiometry, phase stability, and liquid-phase formation was compiled to provide guidance for the selection and interpretation of anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(115 citation statements)
references
References 65 publications
6
105
0
Order By: Relevance
“…[8][9][10][11] In this letter, we report ion-milling studies on YBCO grown by the BaF 2 ex situ process on IBAD-YSZ buffered metal substrates. The details of the BaF 2 ex situ growth process 7,12 and preparation of IBAD-YSZ buffered metal tapes 13 are given elsewhere. Briefly, precursor layers of the desired thickness were prepared by vacuum deposition using three electronbeam sources onto a ''cold'' substrate; the layers were subsequently converted into epitaxial YBCO by annealing in a furnace under flowing gas conditions at atmospheric pressure.…”
mentioning
confidence: 99%
“…[8][9][10][11] In this letter, we report ion-milling studies on YBCO grown by the BaF 2 ex situ process on IBAD-YSZ buffered metal substrates. The details of the BaF 2 ex situ growth process 7,12 and preparation of IBAD-YSZ buffered metal tapes 13 are given elsewhere. Briefly, precursor layers of the desired thickness were prepared by vacuum deposition using three electronbeam sources onto a ''cold'' substrate; the layers were subsequently converted into epitaxial YBCO by annealing in a furnace under flowing gas conditions at atmospheric pressure.…”
mentioning
confidence: 99%
“…All samples consisted of a deformation textured Ni substrate with a Ni/CeO 2 or Y 2 O 3 /yttria-stabilized zirconia (YSZ)/CeO 2 buffer layer structure. The YBCO layers were grown by the barium fluoride 6 or trifluoroacetate 7 methods. All patterned links ͑inter-and intragrain͒ were 10 m wide and 30 m long.…”
mentioning
confidence: 99%
“…These results can be interpreted in terms of the phase diagram of YBCO, O 2 partial pressure vs. the reciprocal temperature, reported by Hammond and Bormann [5], Matijasevic et al [6], and Feenstra et al [7].…”
Section: Resultsmentioning
confidence: 99%
“…Kuhle et al reported the effect of Ar dilution in PLA deposition using O 2 gas on the surface morphology and the superconducting properties [4]. The effect of oxidation gas pressure for in situ preparation [5,6] and post-deposition annealing [7] of the YBa 2 Cu 3 O x (YBCO) films in various oxidation environments were also investigated. In most of these experiments, the excitation effect and the thermodynamical effect of ambient oxidation gas on the structure and properties of YBCO films are not necessarily discriminated.…”
Section: Introductionmentioning
confidence: 99%